Mesotrione alters the structure of network interactions between soil microbes and affects C and N cycling functions - Wu, Xiaojun; Feng, Ruicao; Cai, Liuti; Lu, Ning; Lin, Musen; Gao, Gui; Wang, Ying; Peng, You; Wang, Hancheng (Frontiers in Microbiology, 2026)
Mesotrione is a widely used herbicide in corn production. However, its persistence in soil following application can cause significant damage to subsequent crops such as tobacco. Despite its widespread use, it remains unclear how mesotrione applications affect soil carbon and nitrogen cycling, as well as whether they alter soil microbial communities. Here, we conducted a 2-month greenhouse experiment to investigate changes in functional C and N cycling genes as well as the structural assembly of soil microbial communities following mesotrione application at 180 (T1) and 900 (T5) g a.i. ha−1. The results showed that total nitrogen, available nitrogen and organic matter in the soil were significantly reduced at both 30 and 60 days after mesotrione application (T1 and T5) compared to untreated control. Mesotrione significantly reduced the α-diversity of soil microbial communities at 10 days, and suppressed metabolic activity across multiple carbon sources over extended periods. The structure of the soil microbial exhibited complex dynamics from 1 to 60 days after mesotrione application, with a significant increase in the relative abundance of Nocardioides observed specifically in the T5 treatment. The effects of mesotrione on functional genes mediating the same C-cycling processes (carbon fixation pathway and methane metabolism) were differential. Mesotrione exhibited inhibitory effects on functional genes involved in nitrification, denitrification, and assimilatory nitrate reduction processes within the soil N-cycling, as well as promoting effects on those mediating nitrogen fixation. Network analyses revealed that soil microbial communities exhibited greater complexity and higher connectivity under high concentrations of mesotrione stress, with low abundance microbial genera forming a highly connected modular center. The number of microbial genera associated with key functional genes involved in soil C and N cycling increased following mesotrione application. Taken together, our findings provide theoretical insights into the microbial mechanisms underlying mesotrione’s impacts on soil carbon and nitrogen cycling.